3D Lattice Boltzmann simulations for water droplet's impact and transition from central-pointy icing pattern to central-concave icing pattern on supercooled surfaces. Part I: Smooth surfaces. (June 2021) - Ma, Zhiyuan; Xiong, W.; Cheng, P.
Highlights: A water droplet's impact and its subsequent spreading, recoiling and freezing on a smooth substrate at a supercooled temperature is studied numerically. Simulated results confirm that a water droplet after its impact on a smooth surface at a supercooled temperature can form either a central-pointy icing pattern or a central-cave icingpattern. A map showing effects of contact angle and Stefan number on the formation of central-pointy icing or central-cave icing patterns on a smooth surface is presented. Abstract: A water droplet's impact and its subsequent spreading, recoiling and freezing on a smooth substrate at a supercooled temperature is studied numerically using a 3D pseudo-potential lattice Boltzmann method, in combination with a solid-liquid phase-change model with volume expansion of water at 0°C taken into consideration. Simulated results show that a water droplet after its impact on a smooth surface at a supercooled temperature can form either a central-pointy icing pattern with a single ice peak, or a central-concave icingpattern in a donut shape, depending on the contact angle and the supercooled degree of the wall. Itisshown that the recoiling motion of the droplet after its impact on the supercooled substrate plays the dominant role in the formation of the central-pointy icing or central-concave icing pattern. The central-pointyicingpattern is formed on a substrate having a large contact angle where the recoiling motion of the droplet is strong while the central-concave icing pattern is formed on a substrate having a high degree of supercooled temperature (i.e., a large Stefan number) where the recoiling motion is terminated prematurely because of early nucleation of freezing on the supercooled substrate. The volume expansion during liquid to ice phase-change process at 0°C does affect the movement of the liquid phase although its effect on the formation of icing patterns is small. Effects of movement of freezing fronts on the shape of the icing patterns are illustrated. At fixed values of We = 320 and Re = 164.9, a map showing effects of contact angle and Stefan number (bottom wall temperature) on the formation of central-pointy icing or central-concave icingpatterns after a water droplet's impact (with D0 = 100 and Pr = 13.5) on smooth supercooled surfaces is presented.